Akka Larencja – kobieta pogranicza - Hartleb-Kropidło, Barbara (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2022)
In this article we analyze various versions of the myth of Acca Larentia preserved in the works of ancient annalists, historians, poets, and writers. This mysterious figure, which appears in various creations in literature, plays the role of a caring nurse of Romulus and Remus, a heir of wealthy Tarutius or a beautiful and noble prostitute her property to the Roman people. She is also presented as the mother of twelve brothers, who after the death of one of them and his replacement by Romulus, founded the college of priests called the Arval Brothers. Despite such different and seemingly inconsistent versions of the myth, for ancient Romans, Acca Larentia remains a figure with a coherent and congruent image. This character nes elements of the original agrarian culture with elements of other myths, which create a figure manifesting many features merged during the long process of shaping her personality. All of them reflect the parts of history and identity of the Romans that remain important for them despite the essential changes in their circumstances and manner of living.
Keywords: Akka Larencja; Larentalia; Romulus; mit; historiografia; Katon Starszy